Main features of the aquatic regime of Galanthus angustifolius G. Koss in natural habitat - S. Kh. Shkhagapsoev; L. Kh. Tkhazaplijeva (Юг России: экология, развитие)
The research of water regime features of Galanthus angustifolius G. Koss in dependence of soil and plant age is considered.